Optimalisasi Penerbitan Surat Berharga Syariah Negara (SBSN) Pada Indstri Keuangan Syariah - Wahid, Alif Rodliya (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2019)
State Sukuk (Surat Berharga Syariah Negara) is an instrument of investment activities issued by the government. Sukuk can be used as a development of infrastructure that is primarily focused on advancing the nation